Lean Six Sigma and Big Data Analytics: An integrated Approach for Data-Driven Decision Making (Global Journal of Management and Business Research, 2023)
This paper explores the integration of lean six sigma and AI technologies and how they can enhance each other's value. The paper introduces AI technologies such as Big Data Analytics, Data Mining and Machine Learning and explains how they can be applied within Lean Six Sigma frameworks. The paper also proposes a synergetic framework that combines AI tools and Lean Six Sigma methodologies. The paper is structured as follows. Section 1 is the introduction. Section 2 gives a brief overview of Lean Methodologies and their frameworks. Section 3 and 4 describe AI technologies, focusing on Big Data Analytics and Machine Learning (ML). Section 5 presents the synergetic framework that embeds AI tools into Lean Six Sigma (LSS) frameworks.
Keywords: lean six sigma (LSS; artificial intelligence AI; big data analytics; machine learning (ML); DMAIC